2019
DOI: 10.3390/cells8080844
|View full text |Cite
|
Sign up to set email alerts
|

EGFR/ErbB Inhibition Promotes OPC Maturation up to Axon Engagement by Co-Regulating PIP2 and MBP

Abstract: Remyelination in the adult brain relies on the reactivation of the Neuronal Precursor Cell (NPC) niche and differentiation into Oligodendrocyte Precursor Cells (OPCs) as well as on OPC maturation into myelinating oligodendrocytes (OLs). These two distinct phases in OL development are defined by transcriptional and morphological changes. How this differentiation program is controlled remains unclear. We used two drugs that stimulate myelin basic protein (MBP) expression (Clobetasol and Gefitinib) alone or combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 69 publications
0
43
0
Order By: Relevance
“…While oligodendrogenesis requires the upregulation of EGFR signaling, the final step of oligodendrocytes maturation, that is axon engagement, is fostered by EGFR inhibition ( Figure 6 B). In fact, it was demonstrated that EGFR inhibition stimulates MBP expression in premyelinating oligodendrocytes and cotreatment with Clobetasol and Gefitinib, which inhibit EGFR, favors MBP expression and localization of phosphatidylinositol 4,5-bisphosphate (PIP2) in endosome-like structures leading to membrane expansion and, consequently, to axon engagement [ 99 ].…”
Section: Egfr Functions In the Cnsmentioning
confidence: 99%
“…While oligodendrogenesis requires the upregulation of EGFR signaling, the final step of oligodendrocytes maturation, that is axon engagement, is fostered by EGFR inhibition ( Figure 6 B). In fact, it was demonstrated that EGFR inhibition stimulates MBP expression in premyelinating oligodendrocytes and cotreatment with Clobetasol and Gefitinib, which inhibit EGFR, favors MBP expression and localization of phosphatidylinositol 4,5-bisphosphate (PIP2) in endosome-like structures leading to membrane expansion and, consequently, to axon engagement [ 99 ].…”
Section: Egfr Functions In the Cnsmentioning
confidence: 99%
“…Mice that lack RxRγ fail in adult oligodendrogenesis [38]. Consistent with this finding, many of the promyelinating drugs isolated in phenotypical screens upregulate both MBP expression and RxRγ [33,37]. Using purified primary OPCs isolated from control and OPC-specific Chd7-deficient mice, it has been shown that TFs such as Sox10, Olig2, Nkx2.2, and Ascl1 are key regulators of OL differentiation by directly controlling transcription of genes implicated in chromatin remodeling.…”
Section: Molecular Aspects Of Opc Differentiation In Murine Models Ofmentioning
confidence: 77%
“…Here, we review the main contributions that have led to the current state-of-the-art of in vitro models, drug screening, and validation studies. Although at the moment it is early to evaluate how these findings will impact clinical therapies ( Table 1 and Table 2 ), they have provided a wealth of knowledge on the mechanisms of adult CNS remyelination [ 1 , 4 , 6 , 7 , 9 , 37 ]. Furthermore, we discuss recent biological findings in the CNS remyelination process, as we think new drug discovery programs will have to focus on recent advances in the molecular understanding of OPC differentiation in man compared to murine models.…”
Section: Introductionmentioning
confidence: 99%
“…Clobetasol acts as a Smoothened (Smo) agonist to upregulate myelin gene expression in the Oli-neuM cell line, and RxRγ activation is required for MBP expression after clobetasol treatment [25]. RXRγ upregulation due to clobetasol treatment may contribute to coordinating the lipid metabolism with MBP expression under EGFR and Smo signaling in myelinating OL [26]. As a corticosteroid, clobetasol can modulate glucocorticoid receptor signaling in the cytoplasm of cells.…”
Section: Discussionmentioning
confidence: 99%